Value of nitroglycerin test in the diagnosis of heart failure in emergency department patients with undifferentiated dyspnea. Issue 7 (2nd June 2021) - Sekma, Adel; Bel Haj Ali, Khaoula; Jeddi, Camilia; Ben Brahim, Nadia; Bzeouich, Nasri; Gannoun, Imen; Trabelssi, Imen; Laouiti, Kamel; Grissa, Mohamed Habib; Beltaief, Kaouthar; Zohra, Dridi; Asma, Zorgati; et al.
Abstract: Background: Rapid diagnosis of heart failure (HF) in acutely dyspneic patients can be challenging for emergency department (ED) physicians. Hypothesis: Cardiac output (CO) change with sublingual nitroglycerin (NTG) could be helpful in the diagnosis of HF in patients with acute undifferentiated dyspnea. Materials and Methods: A prospective study of patients >18 years admitted to the ED for acute dyspnea. Using thoracic bioimpedance, we measured CO change at baseline and after sublingual administration of 0.6 mg of NTG. HF was defined on the basis of clinical examination, pro‐brain natriuretic peptide levels, and echocardiographic findings. Diagnostic performance of delta CO was calculated by sensitivity, specificity, likelihood ratio and receiver operating characteristic (ROC) curve. Results: This study included 184 patients with mean age of 64 years. Baseline CO was comparable between the HF group and the non‐HF group. At its best cutoff (29%), delta CO showed good accuracy in the diagnosis of HF with a sensitivity, specificity, positive and negative likelihood ratios of 80%, 44%, 57%, and 66% respectively. Area under ROC curve was 0.701 [95% CI 0.636–0.760]. The decrease of CO with sublingual NTG was significantly higher in patients with HFpEF compared with those with HFrEF. Multivariate analysis, showed that delta CO was an independent factor associated with HF diagnosis [OR 0.19 (95% CI 0.11–0.29); p < .001]. Conclusions: Our study showed that CO change with sublingual nitroglycerin is a simple tool that may be helpful for the diagnosis of HF in ED patients with undifferentiated dyspnea.